JMJD1A, H3K9me1, H3K9me2 and ADM expression as prognostic markers in oral and oropharyngeal squamous cell carcinoma - Maia, Lucas de Lima (PLoS One, 2018)
AIMS: Jumonji Domain-Containing 1A (JMJD1A) protein promotes demethylation of histones, especially at lysin-9 of di-methylated histone H3 (H3K9me2) or mono-methylated (H3K9me1). Increased levels of H3 histone methylation at lysin-9 (H3K9) is related to tumor suppressor gene silencing. JMJD1A gene target Adrenomeduline (ADM) has shown to promote cell growth and tumorigenesis. JMJD1A and ADM expression, as well as H3K9 methylation level have been related with development risk and prognosis of several tumor types. METHODS AND RESULTS: We aimed to evaluate JMJD1A, ADM, H3K9me1 and H3K9me2expression in paraffin-embedded tissue microarrays from 84 oral and oropharyngeal squamous cell carcinoma samples through immunohistochemistry analysis. Our results showed that nuclear JMJD1A expression was related to lymph node metastasis risk. In addition, JMJD1A cytoplasmic expression was an independent risk marker for advanced tumor stages. H3K9me1 cytoplasmic expression was associated with reduced disease-specific death risk. Furthermore, high H3K9me2 nuclear expression was associated with worse specific-disease and disease-free survival. Finally, high ADM cytoplasmic expression was an independent marker of lymph node metastasis risk. CONCLUSION: JMJD1A, H3K9me1/2 and ADM expression may be predictor markers of progression and prognosis in oral and oropharynx cancer patients, as well as putative therapeutic targets.